2006
DOI: 10.1530/eje.1.02069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gastric bypass on the GH/IGF-I axis in severe obesity – and a comparison with GH deficiency

Abstract: Objective: Overfeeding suppresses GH secretion and makes evaluation of a suspected GH deficiency (GHD) difficult. In normal weight subjects, gender is known to influence GH concentrations, which is most apparent in the ambulatory, morning-fasted state. In this study, we examined the GH/IGF-I axis in obese men and women and the effect of surgically induced weight loss. Design: Sixty-three subjects (body mass index (BMI) 45^6 kg/m 2 ; 54 women, 9 men) were studied prior to, and 6 and 12 months following Roux-en-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
38
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 53 publications
11
38
0
1
Order By: Relevance
“…However, both ultrafiltrated free IGF-I as well as dissociated free IGF-I levels M a n u s c r i p t 7 have been measured and both found to be significantly decreased in obese women (73). This is in accordance with the previous reported decreased IGF-I/IGFBP-3 molar ratio, a rough estimate of free, biologically active IGF-I, in obesity (26,70) and the normalisation after diet-induced or surgical-induced weight loss consistent with the transient GH-deficient state (26,70). The previous observed differences in measured values of fasting free IGF-I could be due to diurnal induced variations in free IGF-I, IGFBP-1 levels, fasting induced or other hour-to-hour factors influencing the amount of free IGF-I.…”
Section: The Gh-insulin-like-growth-factor-i (Igf-i) Axis In Obesitysupporting
confidence: 89%
“…However, both ultrafiltrated free IGF-I as well as dissociated free IGF-I levels M a n u s c r i p t 7 have been measured and both found to be significantly decreased in obese women (73). This is in accordance with the previous reported decreased IGF-I/IGFBP-3 molar ratio, a rough estimate of free, biologically active IGF-I, in obesity (26,70) and the normalisation after diet-induced or surgical-induced weight loss consistent with the transient GH-deficient state (26,70). The previous observed differences in measured values of fasting free IGF-I could be due to diurnal induced variations in free IGF-I, IGFBP-1 levels, fasting induced or other hour-to-hour factors influencing the amount of free IGF-I.…”
Section: The Gh-insulin-like-growth-factor-i (Igf-i) Axis In Obesitysupporting
confidence: 89%
“…This may nonetheless be attenuated, in light of the participants' loss of weight after surgery. GH levels are suppressed in obesity (21), and Corneli et al (22) found a mean GH response of ;30 mg/L in subjects with a BMI of ;30 kg/m 2 who were subjected to a GH-releasing hormone-arginine test compared with the rise to 15 mg/L during postsurgery hypoglycemia in the current study (BMI 30.1 kg/m 2 ). Insulin levels during clamps were ;25% lower postsurgery versus presurgery, and the absolute insulin amount infused was ;12% lower after surgery (data not shown), indicating increased insulin clearance, and more so if adjustments to body surface are performed.…”
Section: Discussionsupporting
confidence: 53%
“…Here, we subjected patients before and after undergoing GBP surgery to hypoglycemia and examined symptoms and hormonal and autonomic nerve responses. Twelve obese patients without diabetes (8 women, mean age 43.1 years [SD 10.8] and BMI 40.6 kg/m 2 [SD 3.1]) were examined before and 23 weeks (range [19][20][21][22][23][24][25] after GBP surgery with hyperinsulinemic-hypoglycemic clamp (stepwise to plasma glucose 2.7 mmol/L). The mean change in Edinburgh Hypoglycemia Score during clamp was attenuated from 10.7 (6.4) before surgery to 5.2 (4.9) after surgery.…”
mentioning
confidence: 99%
“…1 In the past few years an increasing number of patients with severe hypoglycemia including neuroglycopenia as a result of endogenous hyperinsulinemia in the postgastric bypass setting have been reported. [3][4][5][6] These patients present with severe hypoglycemic symptoms including visual disturbances, altered mental status, seizures, and loss of consciousness, often postprandially. Nesidioblastosis has been most widely recognized in infants.…”
mentioning
confidence: 99%